Desain Pembelajaran Operasi Hitung Bilangan dengan Pembelajaran Kontekstual dalam Meningkatkan Literasi Numerasi Matematika Siswa - Rulia Aulia; Nila Hayati; Zaotul Wardi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to develop a contextual-based mathematics learning module to improve mathematical numeracy literacy among fourth-grade elementary school students, particularly on arithmetic operations. This research employed a Research and Development (R&D) design using the ADDIE development model consisting of analysis, design, development, implementation, and evaluation stages. The research subjects were 22 fourth-grade students at SDN 2 Siryawangi. The instruments used included expert validation sheets, teacher and student response questionnaires, and numeracy literacy tests. Data were analyzed using a qualitative descriptive approach supported by the N-Gain test to measure students’ improvement after using the module. The findings indicate that the developed module meets the criteria of validity, practicality, and effectiveness. This is supported by the validation results from material and media experts, each obtaining an average score of 95%, which is categorized as highly valid. In addition, teacher responses of 75% and student responses of 88% show that the module is practical and feasible to be used in the learning process. Furthermore, the effectiveness test results, based on an N-Gain score of 84%, demonstrate a high-level improvement in numeracy literacy. Therefore, this module is feasible to be implemented as an alternative teaching material for contextual learning in elementary schools.